Developing the Potentials of Muslim Students Through Academic Collaboration of Indonesian-Malaysian Institutions - Rusmana, Dadan; Qodim, Husnul; Supiana, Supiana; Setiana, Wiryo; Rahman, Mohammad Taufiq (FISIP UIN SGD Bandung, 2024)
This study aims to analyze the role of collaboration between Sunan Gunung Djati State Islamic University of Bandung, Federal Territory Islamic Religious Council (MAIWP), and the University of Malaya in developing the potential of Muslim students. Using a qualitative approach with a descriptive method through case studies, data were obtained through interviews, observations, and documentation from the International Seminar on Islam in the Archipelago. The results of the study show that this collaboration contributes to the exchange of science and educational practices between countries, but there are still obstacles to its implementation, such as limited financial and bureaucratic support. The conclusion of this study emphasizes the importance of a more structured framework to support the sustainability of the collaboration. Contribution: This research contributes to the development of cross-border academic collaboration strategies in Islamic education as well as strengthening academic relations between Indonesia and Malaysia.